Membaca Kritis Novel Api Tauhid Karya Habiburrahman El Shirazy untuk Memperkuat Budaya Literasi - Ahmad Husin; Andi Wapa (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
Critical thinking in this case, where critical reading ability is the ability to read which focuses on the process of using and connecting previously held knowledge with what is written in the text of the novel Api Tauhid by Habiburrahman El Shirazy. Critical reading activities can take the form of critically understanding the ideas in the text by being questioning what the author says, trying to apply what is in the novel to new situations, analyzing and synthesizing what is written, and evaluating critically by linking existing knowledge. previously owned the content of the novel. Critical reading is also called advanced reading or reading comprehension, the activity starts with understanding the novel text and ending with evaluating the reading. All critical reading activities are basically managing novel texts critically by using learning strategies that are appropriate to the purpose of reading. The type of research used in this research is qualitative research. This is based on the disclosure of symptoms as a whole in accordance with the context of a natural setting. It is said that the research setting took place naturally because in this research, data was obtained by researchers from planning, implementing and evaluating learning to critically read the novel Api Tauhid by Habiburrahman El Shirazy carried out by students.